Case report: Filamin A mutation lung disease recognized in an 11‐year‐old child. Issue 1 (7th November 2022) - West, Tahira; Williamson, Nikita; Akhter, Javeed
Abstract: The loss of function (LOF) due to mutations in the Filamin A (FLNA) gene may result in abnormality of the FLNA protein. Of the many clinical syndromes, this condition may produce chronic lung disease, which usually presents and is diagnosed in the infant/toddler age group. Its clinical pattern may mimic broncho‐pulmonary dysplasia. It is part of the entities included in childhood interstitial lung disease group of disorders. We are herein reporting a patient that was diagnosed with FLNA‐associated lung disease at 11 years of age. This case provides a unique insight into the long‐term course of lung disease in this illness and broadens our understanding of the spectrum of its presentation. Although the patient had symptoms early in life, the diagnosis was not entertained because of the rarity of the disorder, its atypical and clinically mild presentation, and discontinuous care due to parents moving to different cities for employment reasons. Her presentation to our institution was for pneumonia. Due to highly unusual chest X‐ray images, asthenia, and early clubbing, an extensive workup included further imaging and a lung biopsy. The final diagnosis was confirmed by the detection of FLNA LOF gene mutation.